2021
DOI: 10.1109/tpwrd.2020.3035718
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Oil-Immersed Medium Frequency Transformer for Offshore HVDC Wind Farms

Abstract: Har du en dröm, får du jaga den. Om drömmen är paj, får du laga den. Har du ingen dröm, får du skapa en och sätta stop för dem som vill skada den. Så låt dem titta på dig. Ja! de kan döma dig. Fortsätt vara du! Jag lovar att det lönar sig.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…The results of that work were expected to be used by offshore windfarm integration-network designers and manufacturers of equipment for wind farms, as well as manufacturers of MFTs for insulated DC/DC converters. Furthermore, during the previous phases of the project, design and construction processes of prototype transformers that can withstand a high DC offset voltages were reported [5,6] and the challenges in designing such transformers were reviewed [7]. In the present paper, the next step of the project is reported, which focuses on implementation of an environmentally friendly solution of the insulation system of MFT, based on biodegradable transformer oil and Oil Impregnated Pressboard (OIP).…”
Section: Hvdc Cablementioning
confidence: 99%
See 1 more Smart Citation
“…The results of that work were expected to be used by offshore windfarm integration-network designers and manufacturers of equipment for wind farms, as well as manufacturers of MFTs for insulated DC/DC converters. Furthermore, during the previous phases of the project, design and construction processes of prototype transformers that can withstand a high DC offset voltages were reported [5,6] and the challenges in designing such transformers were reviewed [7]. In the present paper, the next step of the project is reported, which focuses on implementation of an environmentally friendly solution of the insulation system of MFT, based on biodegradable transformer oil and Oil Impregnated Pressboard (OIP).…”
Section: Hvdc Cablementioning
confidence: 99%
“…In this work, the properties of the biodegradable dielectric oil and OIP are measured under an extensive effort and presented, and the results are used for the insulation design of an MFT introduced in the paper. Additionally, a 10 MVA HVDC MFT with an insulation system using biodegradable oil and OIP is designed based on the method developed previously and verified by experimental testing [5]. Consequently, the performance of the ester-based insulation system is analyzed and compared to the case when mineral oil is used.…”
Section: Hvdc Cablementioning
confidence: 99%
“…Reducing the HV winding height is also done in order to keep the HV winding far from the core edges at the top and bottom. To minimize high electric stresses at the winding's sharp edges, the commonly used rectangularshaped windings [7] are replaced with circular windings which are more suitable for MFTs with high voltage applications. As a result of using circular windings, the core segments are also distributed along the circumference of the winding region.…”
Section: Test Object and Experimental Verificationmentioning
confidence: 99%
“…Also, in parallel-input series-output DC-DC converters in all-DC offshore wind farms [6], there is a high DC offset voltage between the primary and secondary windings inside MFT. This requires an appropriate insulation system which enforces further restrictions on reducing the distances between windings which is extensively investigated by the authors in their previously reported activity [7]. Recent studies show that, from a practical point of view, for achieving a certain power and specific voltage conditions in a high-power MFT, there is a specific range for the optimal operating frequency which is 6-20 kHz [8]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…An insufficient leakage inductance can adversely affect the converter efficiency while higher values of leakage inductance can cause an unnecessary reactive power circulation within the converter [4]. Therefore, the design of an MFT should fulfill the criteria of having a determined leakage inductance in addition to meet the other design requirements such as the specified isolation, efficiency and the thermal requirements [3], [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%